Metformin Ameliorates Diabetic Cardiomyopathy by Activating the PK2/PKR Pathway - Yang, Zhen; Wang, Min; Zhang, Yuchen; Cai, Fei; Jiang, Botao; Zha, Wenliang; Yu, Wei (Frontiers in Physiology, 2020)
Diabetic cardiomyopathy (DCM) is a complication of diabetes that can cause damage to myocardial structure and function. Metformin (Met) is a widely used type 2 diabetes treatment and exerts cardioprotective effects through multiple pathways. Prokineticin 2 (PK2) is a small molecule-secreted protein that plays a pivotal part in cardiomyocyte survival and angiogenesis. However, the role of Met in regulating the PK2 signalling pathway in DCM remains unclear. This experiment explored the effect of Met on high glucose-induced injury through the PK2/PKR pathway in diabetic cardiomyopathy in vivo and in vitro. Cardiomyocytes isolated from adult or AKT knockout mice were treated with high glucose (HG, 33 mM) combined with a PK2 or AKT inhibitor. The heart contraction properties were evaluated based on cell shortening, which included resting cell length, peak shortening (PS), maximum speed of shortening/relengthening (±dL/dt), time to 90% relengthening (TR90) and time to peak shortening (TPS). Streptozotocin-induced diabetic mice and HG-incubated H9c2 cardiomyoblast cells were treated with Met, the PK2 antagonist (PKRA7) or an AKT inhibitor to evaluate cardiac function, myocardial structure and the PK2/PKR pathway. Prolonged TR90 and decreased PS and ±dL/dt caused by HG were partly restored by PK2 in cardiomyocytes, but its effects were negated by the AKT inhibitor and in AKT knockout mice. Diabetic mice had myocardial fibre breakage, fibrosis, severe mitochondrial vacuolization, abnormal myocardial systolic and diastolic function and apoptosis, and Met reversed these changes. Moreover, the expression of PK2, PKR1, PKR2, p-AKT and p-GSK3β was decreased in diabetic mice and rescued by Met. Likewise, H9c2 cells exposed to HG showed reduced PK2/PKRs expression and decreased p-AKT and GSK3β expression, and these effects were nullified by Met; however, the effects of Met were negated after intervention with PKRA7 or AKT inhibitor. These results suggested that Met can activate the PK2/PKR-mediated AKT/GSK3β pathway, thus improving cardiac function and alleviating apoptosis in DCM.